Study on Interfacial Bonding Properties of NiTi/CuSn10 Dissimilar Materials by Selective Laser Melting - Changhui Song; Zehua Hu; Yunmian Xiao; Yang Li; Yongqiang Yang (Micromachines, 2022)
The dissimilar materials bonding of NiTi alloy with shape memory effect (SME) and CuSn10 alloy with good ductility, electrical conductivity, and thermal conductivity can be used in aerospace, circuits, etc. In order to integrate NiTi and CuSn10 with greatly different physical and chemical properties by selective laser melting (SLM), the effects of forming interlayers with different SLM process parameters were explored in this study. The defects, microstructure, and component diffusion at the interface were also analyzed. Columnar grain was found along the molten pool boundary of the interfacial region, and grains in the interfacial region were refined. Elements in the interfacial region had a good diffusion. Phase identifying of the interface showed that Ni4Ti3 was generated. The analysis showed that the columnar grain, refined grains in the interfacial region, and a certain amount of Ni4Ti3 could strengthen the interfacial bonding. This study provides a theoretical basis for forming NiTi/CuSn10 dissimilar materials structural members.